2021
DOI: 10.1186/s12944-021-01576-9
|View full text |Cite
|
Sign up to set email alerts
|

Medium & long-chain acylcarnitine’s relation to lipid metabolism as potential predictors for diabetic cardiomyopathy: a metabolomic study

Abstract: Background Acylcarnitine is an intermediate product of fatty acid oxidation. It is reported to be closely associated with the occurrence of diabetic cardiomyopathy (DCM). However, the mechanism of acylcarnitine affecting myocardial disorders is yet to be explored. This current research explores the different chain lengths of acylcarnitines as biomarkers for the early diagnosis of DCM and the mechanism of acylcarnitines for the development of DCM in-vitro. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Acylcarnitines are important metabolites in cellular energy metabolism pathways, particularly beta-oxidation. 23 Reduction in some acylcarnitines has been reported as part of the metabolic changes associated with MS. 2426 In contrast with these results, studies of other systemic diseases, like diabetes, have found acylcarnitines to be elevated in these states as a possible result of mitochondrial dysfunction and impaired fatty acid oxidation. 27 It has also been shown that medium-chain acylcarnitines (C8–C14) can induce the production of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 94%
“…Acylcarnitines are important metabolites in cellular energy metabolism pathways, particularly beta-oxidation. 23 Reduction in some acylcarnitines has been reported as part of the metabolic changes associated with MS. 2426 In contrast with these results, studies of other systemic diseases, like diabetes, have found acylcarnitines to be elevated in these states as a possible result of mitochondrial dysfunction and impaired fatty acid oxidation. 27 It has also been shown that medium-chain acylcarnitines (C8–C14) can induce the production of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 94%
“…Another study carried out by Guasch-Ferré et al (2019) found that SCAC and LCAC levels were significantly associated with high cardiovascular risk in a Mediterranean cohort. Zheng et al (2021) related the high levels of LCACs and MCACs with risk of diabetic cardiomyopathy in nonobese patients. Concerning physiological contents, relative concentrations were estimated by equivalence to IL-ISs (Table S3).…”
Section: Application Of the Developed Methods To Determine Physiologi...mentioning
confidence: 99%
“…In addition, the accumulation of medium-and long-chain acylcarnitine also causes the disorder of adenosine 5 ′ -monophosphate-activated protein kinase (AMPK) signaling pathway, leading to the increase in lipid deposition in myocardial cells, and eventually causing myocardial lipotoxicity, hypertrophy, fibrotic remodeling, and increased apoptosis [23][24][25].…”
Section: L-acetylcarnitine Decanoylcarnitine (C10) Lauroylcarnitine (...mentioning
confidence: 99%